Towards a Double Hybrid VTOL UAV System - Lucena, Alysson; Gonçalves, Luiz (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
We draw complete efforts towards the development of a double hybrid tailsitter UAV system, which is basically composed of a multirotor with 2 electric powertrain sets and a ﬂying wing with combustion powertrain set. Our goal is to design a UAV that diminishes consumption for vertically taking off and landing and to perform the horizontal ﬂight with greatest possible autonomy on ﬂight time and distance. Considering these requirements, the UAV is conceptualized and built as a ﬂying wing propelled by a pusher configuration powerplant, with combustion engine propeller, a multi-engine composed of two powerplant sets with electric motors and propellers, positioned on the leading edge of the wing, and two standard elevation control surfaces and two vertical stabilizers that also have the support function for takeoff and landing. Several takeoff, ﬂight, and transition tests were carried out successfully, but autonomy (time and distance) tests due to the COVID19 pandemic. Results show versatility of the hybrid tailsitter for operations in the ﬂight field, in a limited location. The built prototype has proven to be functional and the hybrid system effective, to date.